GO film on flexible substrate: An approach to wearable colorimetric humidity sensor. (February 2021) - Chi, Hong; Ze, Lim Jun; Zhou, Xuemin; Wang, Fuke
Abstract: Graphene and graphene oxides have outstanding electrical and optical properties, making it particularly interesting in the field of gas sensing. In this study, colorimetric humidity sensor based on graphene oxide (GO) thin film on different substrates was fabricated by using dip coating technique. The fabrication conditions that influence the humidity response were systematically investigated and optimized. Our results indicated that GO thin film on metallized polyethylene terephthalate (mPET) film displayed poor resolution and sensitivity if it was fabricated from aqueous dispersion. However, both spectra resolution and reflectance color of GO film on mPET are enhanced, if it was fabricated from acetone dispersion. It was attributed to the wetting property of solvent that help to form uniform d -spacing of GO sheet assemblies as revealed from XRD analysis. Bending test of the formed GO film on mPET showed an extreme spectra stability upon 10, 000 cycles of bending, suggesting that the devices are quite suitable for flexible device applications in both personal physiological condition monitoring and environment condition change detection. Graphical abstract: Image 1 Highlights: Fabrication of graphene oxide films on flexible substrates by using dip-coating technique. Optical properties of the films were remarkably affected by substrate, pulling rate and solvent. Factors that influence humidity detection were optimized.